2015
DOI: 10.1016/j.molcel.2015.07.016
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the Human and Yeast General Transcription and DNA Repair Factor TFIIH

Abstract: Summary TFIIH is essential for both RNA polymerase II transcription and DNA repair, and mutations in TFIIH can result in human disease. Here, we determine the molecular architecture of human and yeast TFIIH by an integrative approach using chemical crosslinking/mass spectrometry (CXMS) data, biochemical analyses, and previously published electron microscopy maps. We identified four new conserved “topological regions” that function as hubs for TFIIH assembly and more than 35 conserved topological features withi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
135
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 93 publications
(157 citation statements)
references
References 61 publications
21
135
1
Order By: Relevance
“…The resulting model explains why residues K95 and K731 of Rad3 (colored cyan in Fig. 2 C and D) both form cross-links to the core subunits of TFIIH (1,16). Although Rad3 was in close proximity to TFIIE, there was little or no contact between them ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…The resulting model explains why residues K95 and K731 of Rad3 (colored cyan in Fig. 2 C and D) both form cross-links to the core subunits of TFIIH (1,16). Although Rad3 was in close proximity to TFIIE, there was little or no contact between them ( Fig.…”
Section: Resultsmentioning
confidence: 94%
“…For CXMS, TAP-purified editosome complexes were mixed with 2 mM or 5 mM BS3, quenched, digested with trypsin, and peptides were fractionated by strong cation-exchange chromatography and analyzed by MS. Crosslinked peptides were identified by searching the MS data against appropriate databases using pLink (76) and Nexus (48,77). A 5% false-discovery rate was used for both pLink and Nexus searches.…”
Section: Methodsmentioning
confidence: 99%
“…S3). This approach identifies the specific crosslinked amino acid residues and uses distance constraints of the cross-linker to define the residues' proximity, thus revealing potential domain-domain interactions (48). Each ∼20S editosome component, except KREPA4, contains many lysine residues distributed throughout the polypeptides (SI Appendix, Table S3), making editosomes good substrates for this technique.…”
mentioning
confidence: 99%
“…XPD/p44 is part of the multisubunit TFIIH complex, and DNA lesion search, recognition, and verification as well as removal are all tightly regulated via protein-protein interactions (38). Recent studies by Yang and co-workers (28) have demonstrated stalling of XPD helicase activity by bulky DNA lesions (indicating target recognition) in the context of the (seven subunits) TFIIH core complex.…”
Section: Uvrb and Xpd Helicase Activities Are Activated By Proteinmentioning
confidence: 99%